Diatom percolation through soils: a proof of concept laboratory experiment. Issue 5 (2nd October 2015) - Tauro, Flavia; Martínez‐Carreras, Núria; Barnich, François; Juilleret, Jérôme; Wetzel, Carlos E.; Ector, Luc; Hissler, Christophe; Pfister, Laurent
Abstract: Diatoms are unicellular eukaryotic algae that are widely distributed in aquatic environments. In particular, their presence is abundant in stream flows, whereas the instance and transport of cells through subsurface flow is controversial. In this work, we study the transport of diatoms through soils by designing laboratory percolation experiments on undisturbed loamy and sandy soil cores. To label diatom tracers and enhance their detectability, we develop protocols to functionalize frustules of purified diatomite and Conticribra weissflogii cultures with rhodamine 123 and 2‐(4‐pyridyl)‐5[4‐dimethylaminoethyl‐aminocarbamoyl)‐methoxy]phenyloxazole, respectively. Labelled diatoms demonstrate good detectability and resilience under weathering agents. We execute percolation experiments for maximum time domains of approximately 600 min where volumes of water up to 3600 ml are deployed on the soil core surface. Under such experimental conditions, fluorescent diatoms are not recovered in samples of percolated material as per microscopy and spectrofluorometry. While further field studies are needed to fully investigate diatom transport, our findings shed new light on the potential of using biotic tracers for surface hydrological processes. Copyright © 2015 John Wiley & Sons, Ltd.